Pengembangan Media Video Tutorial Pembuatan Variasi Jenis Roti Manis - Ghea Prasita Intan Muda (Syntax Idea)
The purpose of this research is to develop training media in the form of video tutorials and test the feasibility of the resulting media products. This study used the Research and Development method and was developed using the ADDIE development model which includes 5 stages of development, namely: 1) Analyze, 2) Design, 3) Development, 4) Implement, and 5) Evaluation. Trials in the form of media evaluation were carried out to material experts, media experts, and linguists. Meanwhile, user trials are carried out individually, small groups, and field trials. This evaluation and trial was carried out to assess the feasibility of the media as a training medium for sweetbreads. The results of the recapitulation carried out obtained a percentage of 97% by material experts, 91% by media experts, and 91% by linguists. In the individually trial the percentage was 87%, the small group was 91%, and the field trials was 91%. The results of the assessment showed that the video tutorials media for making various types of sweet bread was declared suitable for use as a training medium.